Energy Analysis of Diesel Engine Using Diethyl Ether Under Different Loading Condition - K.Badajena, A.; P.Patnaik, P.; N.Thatoi, D.; K.ACharya, S.; K.Mohanty, U. (International Journal of Engineering and Technology, 2018)
In the recent scenario needless to say consumption of the fossil fuels to make energy available for utilisation in different purposes, leading to the progress of the country, results in the depletion of the underground resources of fuels at a very high rate. The present paper analyses the energy, exergy and performance of a compression ignition (CI) engine using diesel and diethyl ether blends. The results are calculated at different engine loads at a constant compression ratio of 18:1. It is found that the exergy efficiency, maximum combustion gas temperature, brake thermal efficiency increases with increase in engine load. The all blends of fuel the exhaust gas temperature and destruction of exergy increases with increase in load.Â